(untitled) (Journal of Applied Learning and Teaching, 2022)
Budding designers participated in the inaugural Codesign Week 2022, organised by the National University of Singapore. This pilot health district design innovation programme aimed to empower them with skills to reimagine through ideation and prototyping and to articulate their value-driven solutions for an inclusive and engaged Queenstown community. Aligned to the reform effort of Singapore’s Healthier SG, six teams unravelled barriers to elderly and persons with physical or cognitive impairment to live more active and healthy lives. Students co-created ideas around functional living, disease prevention and healthcare delivery together with residents and stakeholders. From pre-/post-survey responses, there was an increase in students’ perceived understanding of inclusive design. Students also felt more confident in critically analysing problems related to persons with reduced cognitive ability and their carers and this resulted in impactful solution ideas enabled by empathetic technology.